An Analysis of the Impact of Service Quality and Passenger Satisfaction on Passenger Preference for Airlines : A Study of the Indian Aviation Sector - Sanyal, Shouvik; Wamique Hisam, Mohammed (International Review of Management and Marketing, 2016)
The primary objective of this paper is to examine the relationship between airline service quality, passenger satisfaction and preference. This study identifies the main factors of airline service quality, passenger satisfaction and preference and proposes a model examining the directional relationship among these three constructs. It is based on an empirical influence of the data collected from 200 passengers with Indian airlines during July and August 2015. The data are analyzed using a variety of statistical techniques. Factor analysis is used to identify the main factors of airline service quality and passenger satisfaction & preference. The segmentation of airline passengers according to their preference levels and psychographic characteristics is performed using cluster analysis techniques. LISREL 8 and path analysis techniques are used to investigate the relationships among the three constructs namely: service quality, passenger satisfaction and passenger preference. The key findings of the study indicate that overall service quality is highly related to both passenger satisfaction and preference. The relationship between passenger and preference toward a specific airline is less clear. Keywords: Service Quality, Passenger's Satisfaction, Passenger's Preference. JEL Classifications: M30, M 31